The Modulatable Stem Cell Niche: Tissue Interactions during Hair and Feather Follicle Regeneration. Issue 7 (10th April 2016) - Chen, Chih-Chiang; Plikus, Maksim V.; Tang, Pin-Chi; Widelitz, Randall B.; Chuong, Cheng Ming
Abstract: Hair and feathers are unique because (1) their stem cells are contained within a follicle structure, (2) they undergo cyclic regeneration repetitively throughout life, (3) regeneration occurs physiologically in healthy individuals and (4) regeneration is also induced in response to injury. Precise control of this cyclic regeneration process is essential for maintaining the homeostasis of living organisms. While stem cells are regulated by the intra-follicle-adjacent micro-environmental niche, this niche is also modulated dynamically by extra-follicular macro-environmental signals, allowing stem cells to adapt to a larger changing environment and physiological needs. Here we review several examples of macro-environments that communicate with the follicles: intradermal adipose tissue, innate immune system, sex hormones, aging, circadian rhythm and seasonal rhythms. Related diseases are also discussed. Unveiling the mechanisms of how stem cell niches are modulated provides clues for regenerative medicine. Given that stem cells are hard to manipulate, focusing translational therapeutic applications at the environments appears to be a more practical approach. Graphical abstract: Highlights: Hair follicle stem cells are regulated by many extra-follicular sources. Signals from the adipose tissue modulate hair stem cell behavior and aging. Upon injury, innate immune response triggers regeneration through quorum sensing. The effects of androgen on hair growth are different in different regions and ages. Seasonal and circadian rhythms modulate the length of hair cycling.